PREVALENCE OF HEPATITIS C VIRUS INFECTION AMONG CHILDREN WITH BETA THALASSEMIA MAJOR IN SULAIMANI - Hasan, Karzan Mohammed; Rashid, Jamal Ahmad; Ghafoor, Ibrahim Khasraw (Journal of Sulaimani Medical College, 2020)
Background Hepatitis C infection is a worldwide problem, especially in multi transfused patients including those with Thalassemia. Thalassemia is one of the inherited diseases, in which there is partial or complete failure of globin chain synthesis. Objectives To evaluate the prevalence of hepatitis C virus infection in multiple blood transfused children with beta-thalassemia major and related risk factors. Patients and Methods A cross-sectional study was conducted on 459 patients (229 males and 230 females) with β-thalassemia major at Sulaimani thalassemia centre from January 2015 to June 2015. Data regarding age, sex, number of blood transfusions, chelating agents and history of splenectomy were obtained. Serum was used for detection of antibodies against hepatitis C virus, hepatitis B surface antibody, hepatitis B surface antigen and, human immunodeficiency virus, also in liver enzymes (Aspartate aminotransferase, Alanine aminotransferase) were checked. Results Sixty-four (13.9%) patients were found to be seropositive for anti-Hepatitis C virus antibodies; this was correlated with age, sex, history of splenectomy, number of blood transfusions and chelating agents. Liver enzymes were significantly higher in infected patients. The risk of exposure to hepatitis C virus was higher than the hepatitis B virus surface antigen and human immunodeficiency virus among the same patients. Conclusion Multi transfused thalassemic patients are at high risk for HCV infection, so more accurate techniques for screening of blood products is suggested.
Keywords: Hepatitis C virus; Thalassemia major; Prevalence